Luminescent core–shell Ca2MoO5:Eu3+-MCM-41 structure for sustained drug release. (December 2021) - Karacolak, A.I.; Emen, F.M.; Kılıç, D.; Kutlu, E.; Ali, M.A.; Körözlü, N.; Demirdogen, R.E.
Abstract: The spherical mesoporous MCM-41 coated with a novel Ca2 MoO5 :Eu 3+ phosphor layer was prepared for the first time. The obtained Ca2 MoO5 :Eu 3+ -MCM-41 was characterized via XRD and FT-IR. The crystal system of the Ca2 MoO5 phase was determined to be orthorhombic, and its space group was found to be Ima 2 (46), and its cell parameters were a = 16.175, b = 5.1514, c = 5.6977 A°; α = β = γ = 90°. The particle dimensions of MCM-41 and Ca2 MoO5 :Eu 3+ -MCM-41 nanoparticles were determined to be 260 nm and 229 nm via scanning electron microscopy analysis. Bortezomib was loaded into the Ca2 MoO5 :Eu 3+ -MCM-41 nanoparticles under scCO2 at 200 bars and 40 °C. The results of the TG analysis showed that the amount of drug-loaded to MCM-41 and Ca2 MoO5 :Eu 3+ -MCM-41 nanoparticles were determined to be 14.02% and 3.02%, respectively. The BET analysis showed that while the specific surface area and pore volume of MCM-41 and Ca2 MoO5 :Eu 3+ before Bortezomib (BTZ) loading were 1, 506 m 2 /g and 267 m 2 /g, respectively, after drug loading these values were found to decrease to 488 m 2 /g and 7.883 m 2 /g. It was determined that BTZ was released from the nanoparticles in a sustained manner over 66 h. The R 2 value, which was calculated to be 0.9739, indicated that the release kinetic of BTZ followed the Korsmeyer–Peppas model. Graphical abstract: Image 1 Highlights: Ca2 MoO5 :Eu 3+ -MCM-41 composite is designed for Bortezomib as a new drug carrier. This system was developed to allow both the monitoring of drug release. The results obtained from the composite showed that it is a strong candidate in drug delivery system.